Specificity and Sensitivity of Cytological Techniques for Rapid Diagnosis of Neoplastic and Non-neoplastic Lesions of Canine Mammary Gland - Sangha, Shivani; Singh, Amarjit; Sood, Naresh Kumar; Gupta, Kuldip (Brazilian Journal of Veterinary Pathology, 2011)
The present study aimed at evaluating diagnostic accuracy and efficacy of cytology for rapid diagnosis and differentiation of various mammary affections of canines and the comparison of cytological findings with that of histopathology. Cytological evaluation was conducted on 33 dog patients having mammary gland lesions. Out of these, 28 cases were diagnosed for various mammary affections and rest five cases were inconclusive on the basis of cytological evaluation. Among various affections, 23 were diagnosed as tumors, four as mastitis and one as a case of steatitis. Comparison of cytological findings with histological diagnoses yielded 70% concordance between the two. For malignant mammary tumours, the correlation was 92.30% while for benign mammary tumours, it was quite low (66.66%). Among malignant tumours (n=13), there was one false positive case (7.69%) and one false negative case (7.69%). One case of mixed mammary tumour was misdiagnosed as simple adenocarcinoma. In benign tumours, only one false negative (3.3%) result was found and there was no false positive result. Various cytological techniques like touch impression, fine needle biopsy and teat fluid cytology were employed and these techniques yielded sensitivity and specificity of cytological diagnoses as 87.5% and 85.7%, respectively. The positive and negative predictive value of cytology for diagnosing mammary tumours was 93.3% and75%, respectively. Overall, cytology was found most accurate in diagnosis of neoplastic lesions followed by inflammatory lesions and hyperplastic lesions.